172k views
4 votes
Use the function f(x)=2x^3-3x^2+7 to complete the exercises

F(-1)= ___
F(1)= ___
F(2)= ___

2 Answers

7 votes

Answer:

f (-1)= 2

f (1)= 6

f (2)= 11

Explanation:

User RankAmateur
by
7.8k points
6 votes

To answer this set of questions, all we have to do is just to substitute the value of x in F(x) to the given f(x) equation.

By substitution and following PEMDAS rule:
F(-1)=2(-1)³-3(-1)²+7=5

F(1)=2(1)³-3(1)²+7=6

F(2)=2(2)³-3(2)²+7=11

Therefore the answers are 5, 6 and 11.

User Jbasko
by
7.9k points